A Method for Creating Microporous Carbon Materials with Excellent CO2‐Adsorption Capacity and Selectivity. Issue 1 (2nd October 2013) - Qian, Dan; Lei, Cheng; Wang, En‐Min; Li, Wen‐Cui; Lu, An‐Hui
Abstract A new synthetic approach for the fabrication of microporous carbon materials (HCMs) by using discrete chelating zinc species as dynamic molecular porogens to create extra micropores that enhance their CO2‐adsorption capacity and selectivity is reported. During the carbonization process, the evaporation of the in situ‐formed Zn species would create additional nanochannels that contribute to the additional micropore volume for CO2 adsorption. The resultant HCMs show an increased number of micropores, with sizes in the range 0.7–1.0 nm and a high CO2‐adsorption capacity of 5.4 mmol g−1 (23.8 wt %) at 273 K and 3.8 mmol g−1 (16.7 wt %) at 298 K and 1 bar, which are superior to those of most carbon‐based adsorbents with N‐doping or high specific surface areas. Dynamic gas‐separation measurements, by using 16 % CO2 in N2 (v/v) as a feedstock, demonstrated that CO2 could be effectively separated from N2 under ambient conditions and shows a high separation factor (S<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sn49wn1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> CO 2/N 2</alternatives>=110) for CO2 over N2, thereby reflecting a strongly competitive CO2‐adsorption capacity. If the feedstock contained water vapor, the dynamic capacity of CO2 was almost identical to that measured under dry conditions, thus indicating that the carbon material had excellent tolerance to humidity. Easy CO2 release could be realized by purging an argon flow through the fixed‐bed adsorber at 298 K, thus indicating good regeneration ability.